Composite Electromagnetic Wave Absorber Made of Soft Magnetic Material Particle and Metal Particle Dispersed in Polystyrene Resin - Sakai, Kenji; Asano, Norizumi; Wada, Yoichi; Guan, Yang; Sato, Yuuki; Yoshikado, Shinzo (IntechOpen, 2011)
None